Production of Activated Carbon by Activation of Tamarind (Tamarindus Indica) Wood Charcoal - Erna Astuti; Zahrul Mufrodi; Shinta Amelia; Muhammad Imam Zulfi; Firdaus Ramadhani (CHEMICA: Jurnal Teknik Kimia, 2023)
Tamarind or Tamarindus indica is a plant originating from Asia and Africa. Tamarind wood has high cellulose that could be activated into activated carbon and modified to become a catalyst from its ingredient nature. This study aims to find optimum conditions for producing activated carbon from tamarind charcoal. Research on the activation of tamarind charcoal begins with reducing the size of charcoal. Then the charcoal was sieved to obtain 40, 60, and 60 mesh charcoal sizes. Furthermore, the charcoal was soaked in HCl (1, 2, 3, 4, and 5 M) for 1 hour, after which it was filtered, and the pH of the charcoal was neutralized by washing using distilled water. The final step is to dry activated carbon in an oven at 105 ºC. Then, the performance of activated carbon is sought by using activated carbon to adsorb dyes in a dye solution. The concentration of the dye solution before and after being adsorbed with activated carbon was measured by UV-vis spectrophotometry at a wavelength of 560 nm.  Adsorption effectiveness is measured. The greatest effectiveness value obtained was 82.31%. Optimum conditions for activating carbon from tamarind charcoal were obtained by activating 60 mesh of carbon using a hydrochloric acid solution of 4 M. The use of activated carbon at different concentrations of dye solutions produces the same optimum conditions. It is proven that activated carbon can be produced from tamarind charcoal.  Tamarind charcoal can be used as an adsorbent material.